Pengembangan Industri Kreatif dan Peran Bank Syariah - Sudarsono, Heri (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2010)
Abstrak: The concept of creative industries has been a feature of academic and policy literature for over a decade. The creative industries are defined in this approach in terms of an industrial classification of what they do. or what they produce and how they do it. The cultural and creative industries fit uneasily into this framework: first, because of they share many generic characteristics of the service economy; and second, because they are to a large extent an outgrowth of the previously non-market economy of cultural public goods and private imagination that seeks new ways of seeing and representing the world. However, the creative industries have come to such recent prominence as these once marginal activities now have significant market value and contribution to individual wealth and GDP. Furthermore, financing creative industry is viewed as a new paradigm to alleviate poverty and bring about development. Problems facing creative industry are, among others, non-viability and dependence on subsidized funds for operations. Given this social role, Islamic banks can provide the much-needed product to creative industry to facilitate their economic upliftment. The paper asserts that Islamic banks can finance the creative industry at no extra cost.